2019
DOI: 10.9734/jpri/2019/v31i230295
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity and Fourier Transform Infrared Spectrometric Characterization of Aqueous Extracts of Acacia senegal and Acacia tortilis on Phytopathogenic Fungi

Abstract: Objective: To evaluate the in vitro antifungal activity of aqueous extracts of Acacia senegal (A. senegal) and Acacia tortilis (A. tortilis) against three phytopathogenic fungi (viz., Alternaria alternata [A. alternata], Helminthosporium rostratum [H. rostratum] and Fusarium solani [F. solani]). Methods: Crude aqueous extracts of A. senegal and A. tortilis at 1%, 2.5% and 5% concentrations were used for screening. Antifungal activities of the extracts were evaluated against three phytopathogenic fungal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Other scholars have also reported similar peaks for A. Senegal and A. tottilis 41 and A. nilotica 37 .…”
Section: Ftirsupporting
confidence: 67%
See 2 more Smart Citations
“…Other scholars have also reported similar peaks for A. Senegal and A. tottilis 41 and A. nilotica 37 .…”
Section: Ftirsupporting
confidence: 67%
“…This agrees with the findings of 2 , establishing that males were more affected by dermatophytes than the female counterpart in their work sampling children from Bauchi state and disagree with the age group with the highest prevalence is 9 -12years only because, they have enrolled children alone in their study. In Maiduguri, 41 also reported that children 7 -11 years (8.1%) are more infected followed by 4 -6years (6.9%) and 12 -16years (3.6%). The isolates recovered according to children also followed the same order at 64%, 25.4%, and 10.5%.…”
Section: Distribution Of Dermatophytes According To Demographic Characteristicsmentioning
confidence: 87%
See 1 more Smart Citation